Evaluating Xen-based virtual routers performance. (8th April 2011) - Bourguiba, Manel; Haddadou, Kamel; Pujolle, Guy
With resurgent interest in virtualisation, router virtualisation seems the next step to servers virtualisation. It is also a key in deploying flexible and isolated virtual networks. In this paper, we evaluate Xen-based virtual routers on top of commodity hardware. Forwarding being achieved through the driver domain networking model, we identify and analyse the throughput limitation through profiling the CPU usage and the memory accesses. In multi-core systems, the memory access latencies are then the bottleneck. Then, we propose in this context a mechanism reducing packets waiting time to be delivered to the virtual router, which guarantees throughput and ensures minimal latency and jitter to delay-sensitive flows, based on the priority they are assigned.